On seperate diagrams, sketch the graphs of:
a) y=(x+3)^2
and
b) y=(x+3)^2+k, where k is a positive constant.
=)
Remember our shifting rules for graphs
$\displaystyle f(x-h)$ shifts the graph of f(x) h units in the x direction.
$\displaystyle f(x) + k$ shifts the graph of f(x) k units in the y direction.
So we need to rewrite a) as follows
Note we will be shifting the graph of $\displaystyle f(x)=x^2$
$\displaystyle f(x+3)=y=(x+3)^2=[x-(-3)]^2$ so since we -3 = h we shift the graph of f(x) three units to the left.
for b)
we will shift f(x) up k units..
Good luck.